A Meta-Analysis of Randomized Controlled Trials on Acupuncture for Amblyopia. (30th April 2013) - Yan, Xingke; Zhu, Tiantian; Ma, Chongbing; Liu, Anguo; Dong, Lili; Wang, Junyan
Abstract : Objective . To assess the evidence of efficacy and safety of acupuncture for amblyopia and analyze the current situation of its clinical setting. Methods . We systemically searched Wanfang, Chongqing Weipu Database for Chinese Technical Periodicals (VIP), China National Knowledge Infrastructure (CNKI), and PubMed. Published randomized controlled trials (RCT) and controlled clinical trials (CCT) that evaluated the effect of acupuncture for amblyopia compared with conventional treatment were identified. The methodological quality of the included trials was assessed based on the Jadad scale. Data synthesis was facilitated using RevMan 5.1. Results . Fourteen trials involving 2662 participants satisfied the minimum criteria for meta-analysis. The evidence showed that the total effective rate of treatment within the group receiving acupuncture was higher than that in conventional group; there were statistically significant differences between groups (polled random effects model (RR) = 1.17, 95% confidence interval (1.11, 1.24), Z = 5.56, P < 0.00001 ). Conclusion . The total effective rate of acupuncture for amblyopia was significantly superior to conventional treatment, indicating that acupuncture was a promising treatment for amblyopia. However, due to the limited number of CCTs and RCTs, especially those of large sample size and multicenter randomized controlled studies that were quantitatively insufficient, we could not reach a completely affirmative conclusion until further studies of high quality are available.